2019
DOI: 10.1021/acs.jmedchem.9b00518
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Aided Identification and Optimization of Tetrahydro-isoquinolines as Novel PDE4 Inhibitors Leading to Discovery of an Effective Antipsoriasis Agent

Abstract: Psoriasis is a common, chronic inflammatory disease characterized by abnormal skin plaques, and the effectiveness of phosphodiesterase 4 (PDE4) inhibitor to lessen the symptoms of psoriasis has been proved. Aiming to find a novel PDE4 inhibitor acting as an effective, safe, and convenient therapeutic agent, we constructed a library consisting of berberine analogues, and compound 2 with a tetrahydroisoquinoline scaffold was identified as a novel and potent hit. The structure-aided and cell-based structure–activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…Recently, Zhang et al. (34) reported the discovery and optimization of Tetrahydro-isoquinolines as novel PDE4D inhibitors. The virtual screening hit compound 2 (IC 50 = 0.27 μM) and optimized lead compound 16 (IC 50 = 0.24 μM) were selected to test the application of DeepScreening.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Zhang et al. (34) reported the discovery and optimization of Tetrahydro-isoquinolines as novel PDE4D inhibitors. The virtual screening hit compound 2 (IC 50 = 0.27 μM) and optimized lead compound 16 (IC 50 = 0.24 μM) were selected to test the application of DeepScreening.…”
Section: Resultsmentioning
confidence: 99%
“…UC is one of the two major forms of inflammatory bowel diseases (IBD), which are closely linked with the precise interaction between gut microbiota, intestinal epithelial barrier function and mucosal immunity 15 . It has been demonstrated that targeting the cAMP-specific PDE4 displayed dramatic effects on suppression of cytokines in multiple inflammatory cells, including macrophages, NKT cells, neutrophils, and T helper cells, and intestinal epithelial cells 35 , 36 , 37 . In the past decades, though the PDE4 inhibitors, rolipram, tetomilast, and roflumilast have been investigated in experimental colitis, the adverse effects impeded the further clinical application 1 , 35 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that targeting the cAMP-specific PDE4 displayed dramatic effects on suppression of cytokines in multiple inflammatory cells, including macrophages, NKT cells, neutrophils, and T helper cells, and intestinal epithelial cells 35 , 36 , 37 . In the past decades, though the PDE4 inhibitors, rolipram, tetomilast, and roflumilast have been investigated in experimental colitis, the adverse effects impeded the further clinical application 1 , 35 . By contrast, apremilast is a well-tolerated PDE4 inhibitor with little gastrointestinal side effects 38 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a growing number of studies have focused on the development of new drugs for psoriasis, including JAK inhibitors, Stat3 inhibitors, PDE4 inhibitors, TRK inhibitors, and AhR agonists (21)(22)(23)(24). However, there was no report yet on the treatment of PEG.…”
Section: Discussionmentioning
confidence: 99%